Comparison of 2D and 3D prediction models for environmental vibration induced by underground railway with two types of tracks - Xu, Qingyuan; Xiao, Zucai; Liu, Tao; Lou, Ping; Song, Xuming (ELsevier, 2015)
Two-dimensional (2D) and three-dimensional (3D) prediction models for environmental vibration induced by underground railway with direct fixation track and steel spring floating slab track are developed and verified. The responses of ground surface calculated by 2D prediction models with various equivalent forces are compared to those calculated by 3D prediction models. The numerical results show that (a) the computational time for each case calculated by 2D prediction models is more than 500 times less than that calculated by 3D prediction models, however, the accuracy of 2D prediction models is relatively lower than 3D prediction models, so 3D prediction models are required for absolute prediction due to their higher accuracy and applicability to a wider range of complex problems; and (b) a suitable equivalent force transfer method for 2D prediction models can improve the prediction accuracy of 2D prediction models, the equivalent forces in 2D prediction models are respectively recommended to use the equivalent wheel-rail force and the equivalent steel spring force averaged over a vehicle length for underground direct fixation track and steel spring floating slab track